Synthesis of novel acid-promoted UIO-66-NH2-MnFe2O4-TiO2- TiNT nanocomposite for high synchronous adsorption of cadmium and methyl orange and conditions optimization by response surface methodology. Issue 5 (24th March 2021) - Nasehi, Pedram; Abbaspour, Seyed Foad; Rafiee, Masoud; Moghaddam, Mojtaba Saei
ABSTRACT: Magnetic nanocomposite UIO-66-NH2 -MnFe2 O4 -TiO2 -TiNT was synthesized for synchronous and selective adsorption of Cd(II) heavy metal and Methyl orange (MO) dye pollutants in the textile wastewater. XRD, SEM, FT-IR, BET and VSM techniques were used. The best conditions were obtained for the independent variables in the synchronous adsorption of Cd(II) and methylene orange (MO) dye for the initial metal concentration, initial MO concentration, pH, adsorbent amount and acid-promoted molar ratio 500 (mg/l), 146.8 (mg/l), 5.5, 0.159 (gr) and 46 respectively. After the adsorption, the adsorbent was removed from the solution well with an external magnetic field. Graphical abstract: